Effect of temperature and external optical feedback on intensity and phase noise characteristics in single-mode fiber grating Fabry-Perot laser - Hisham, Hisham Kadhum; Abas, Ahmad Fauzi; Mahdiraji, Ghafour Amouzad; Mahdi, Mohd Adzir; Mahamd Adikan, Faisal Rafiq (IEEE, 2012)
The combined effect of temperature variation and external optical feedback (OFB) on the relative intensity noise (RIN) and phase noise (FN) characteristics of fiber grating Fabry-Perot (FGFP) laser for the first time, is investigated numerically by modifying the well-known laser rate equations. The temperature dependence (TD) of RIN and FN characteristics is calculated according to TD of laser cavity parameters; not by using the well-known Pankove equation. The effect of external OFB on RIN and FN characteristics is calculated according to its effect on laser threshold carrier density. The simulation of the frequency spectra of RIN and FN are performed by fast Fourier transform (FFT). We show that FBG can be use to control the external OFB level, thereby; controlling noise level of the laser. Results show that the optimum range of working temperature for FGFP laser for low noise characteristic is within ±2 °C from the FBG reference temperature.